Urbanização, planejamento e mudanças climáticas : desafios da capital paulista e da Região Metropolitana de São Paulo - Back, Adalberto Gregório (Universidade Federal de São Carlos, 2016)
The aim of this thesis is to investigate how the recent urban development agenda of São Paulo contributes to overcoming the challenges related to addressing climate change at the local and regional/metropolitan area. Methodology. First we identify the main challenges related to addressing climate change within the MRSP, taking into account the historical development of both the city of São Paulo and the municipalities of Greater São Paulo. We focus our attention on the challenges of urban mobility, taking into account this is the main source of GHG emissions; Housing, given that the main risk areas in the city and region were generated by a lack of adequate housing policies along the urban development of São Paulo; and Environmental Protection because it is related to containment of urban sprawl. Given this identification, we analyze the policy responses to these questions given by the Climate Change Policy and the instruments of the Master Plan of the São Paulo’s city. The results They reveal that the strategies referring to the climate change policy in the city of São Paulo do not address the main determinants involved in generating GHG emissions and vulnerabilities to climate change, nor do they apply to regional / metropolitan challenges. On the other hand, the urban planning instruments act in the municipality promoting the construction and population densification in areas of consolidated urban infrastructure and with mixed use of the soils, promote mechanisms for a social housing construction prioritizing a low income population, incentive to Generation of Jobs in a decentralized way in the city in order to reduce the commuting displacements of great distances and to create mechanisms to contain the irregular and excluding urban sprawl over a rural area of the municipality. In this sense, the regulatory instruments foreseen in the municipality's master plan act on the main causes that generated social and environmental risks and GHG emission levels in the city of São Paulo, and are reflected in the metropolitan context.
Keywords: Planejamento urbano; Mudanças climáticas; Município de São Paulo; Região Metropolitana de São Paulo; Política climática; Urban planning; Climate change; São Paulo’s city; São Paulo’s Metropolitan Region; Climate policy; Mitigation; Adaptation; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS